Vpliv virusov na razvoj avtoimunskih bolezni - Simončič, Eva (Placebo, 2022)
Viral infections are known to influence the development of autoimmune diseases. Among the viruses for which there is the best evidence that they can influence the development of autoimmune disease, are enteroviruses and herpesviruses. Viruses can trigger autoimmunity through several molecular mechanisms, including molecular mimicry, bystander activation, and epitope spreading. Both epidemiological and animal studies have shown that viral infections can also play a protective role against autoimmunity. In this article, I focused on viral infections that may cause type 1 diabetes and systemic lupus erythematosus.
Keywords: autoimmunity, viral infections; Avtoimunost; Avtoimunske bolezni; sistemski lupus eritematozus; sladkorna bolezen tipa 1; systemic lupus erythematosus; type 1 diabetes; Virusi; virusne okužbe